2008
DOI: 10.4049/jimmunol.180.9.6411
|View full text |Cite
|
Sign up to set email alerts
|

Natural Naive CD4+CD25+CD127low Regulatory T Cell (Treg) Development and Function Are Disturbed in Multiple Sclerosis Patients: Recovery of Memory Treg Homeostasis during Disease Progression

Abstract: Patients with relapsing-remitting multiple sclerosis (RR-MS) show a suboptimal CD4+CD25+ regulatory T cell (Treg) function, whereas no Treg alterations are observed in secondary progressive MS (SP-MS) patients. To clarify the difference in Treg activity between early and chronic disease stages in MS, we analyzed the functional capacity and homeostatic parameters of naive CD4+CD25+CD127lowCD45RA+ Tregs (nTregs) and their memory counterparts CD4+CD25+CD127lowCD45RO+ Tregs (mTregs) in untreated MS patients and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
190
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 233 publications
(219 citation statements)
references
References 48 publications
19
190
0
5
Order By: Relevance
“…All analyses were performed on untreated MS patients, because it was reported that treatment strongly influences Treg function. 14 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All analyses were performed on untreated MS patients, because it was reported that treatment strongly influences Treg function. 14 …”
Section: Resultsmentioning
confidence: 99%
“…Also, two independent studies of Venken et al 14 and Haas et al 15 showed that CD31 (PECAM-1) expressing naive Tregs are significantly reduced in the peripheral blood of MS patients. 14,15 CD31 is a 130 kDa transmembrane glycoprotein expressed by endothelial cells, platelets, monocytes, neutrophils and T cell subsets. It was further shown that this adhesion molecule is a marker for recent thymic emigrants (RTE), which are characterized by a high number of T cell receptor excision circles and a low number of cell divisions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, given this relatively high frequency of potentially cross-reactive T cells in the periphery of these individuals, one would perhaps expect a much higher prevalence of MS. Clearly, several peripheral regulatory mechanisms are important in controlling these potentially pathogenic T cells. Several groups, including ours, recently reported impaired immune regulation by CD4CD25 hi regulatory T cells in the peripheral blood of MS patients [21,22]. This may explain why myelin specific T cells expand and persist in the blood of MS patients but not in healthy donors.…”
Section: Tcr Degeneracy and T Cell Regulation: Open Questionsmentioning
confidence: 95%
“…Recent observations suggest that Treg should be equipped with a higher propensity to migrate [6] in order to efficiently suppress effector T cells at target sites of emerging inflammation, as they are hypoproliferative [8,9] and only form 6-10% of the whole CD4 1 T-cell subset. Reports on the accumulation of Treg within the murine CNS during EAE [3] and on containment of EAE relapses by CNS Treg [10,11] 15: p. 72) described the detection of low numbers of Treg in the CNS and in accordance with an earlier study elevated cell numbers in the cerebrospinal fluid of patients with MS [13]. Since increasing evidence supports an antiinflammatory role for Treg at parenchymal sites of inflammation [14], one could speculate that the repeatedly reported impairment in antiproliferative capacity of Treg found in patients with MS [15,16] is just one expression of a more thorough Treg dysfunction.…”
Section: Foxp3mentioning
confidence: 99%
“…Reports on the accumulation of Treg within the murine CNS during EAE [3] and on containment of EAE relapses by CNS Treg [10,11] 15: p. 72) described the detection of low numbers of Treg in the CNS and in accordance with an earlier study elevated cell numbers in the cerebrospinal fluid of patients with MS [13]. Since increasing evidence supports an antiinflammatory role for Treg at parenchymal sites of inflammation [14], one could speculate that the repeatedly reported impairment in antiproliferative capacity of Treg found in patients with MS [15,16] is just one expression of a more thorough Treg dysfunction. Whether Treg migration to sites of active inflammation in the CNS of patients with MS is impaired has been elusive so far.…”
Section: Foxp3mentioning
confidence: 99%